Profil Demografi Orang Dewasa dengan Hipertensi di Wilayah Pesisir Kota Tarakan: Studi Deskriptif - Najihah; Nurman Hidaya (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2026)
Hypertension is the leading cause of premature death worldwide. The trend in the prevalence of hypertension has significantly increased over the past two decades, and many factors contribute to the current burden of hypertension, including modernization, urbanization, lifestyle changes, and socioeconomic status. The incidence of hypertension can be influenced by demographic characteristics. This study aims to identify the demographic characteristics of adults with hypertension. This research is a quantitative study with a descriptive approach. The sample in this study consists of 287 adults with chronic hypertension living in the coastal area of Tarakan Island, obtained using purposive sampling technique with age criteria >18-59 years. The research was conducted in six community health centers in Tarakan City, including Juata, Karang Rejo, Sebengkok, Gunung Lingkas, Mamburungan, and Pantai Amal. The instrument used was a questionnaire sheet containing demographic data such as age, gender, education, occupation, and residence. The research results showed that the average age of adults with hypertension was 51.4 years, the majority were female, had a high school education, worked as housewives, and lived in urban areas. This indicates that hypertension is prevalent among middle-aged groups with certain socio-demographic backgrounds, especially women engaged in domestic activities in urban areas.